Strategi Pengembangan Kurikulum Menghadapi Tuntutan Kompetensi Abad 21 - Hamami, Tasman; Asy’ari, Ari (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2020)
The purpose of this study is to find out how the curriculum development strategy in dealing with the demands of the 21st century, curriculum development according to David Pratt and Winarno Surahmad are more conceptual than material which includes the activities of compiling, implementing, evaluating and refining the curriculum. The research method in this research is the study of literature or literature studies by finding various sources of data derived from relevant books and journal articles that are useful to strengthen the argument of the author The results showed that the curriculum development strategy can be carried out with several steps, namely: identification of needs, searching curriculum materials, curriculum material analysis, curriculum material assessment, decision making adoption of curriculum material.